The bell curve intelligence and class structure in American life - Herrnstein, Richard J.; Murray, Charles A. (The Free Press, 1994)
Breaking new ground and old taboos, Richard J. Herrnstein and Charles Murray tell the story of a society in transformation. At the top, a cognitive elite is forming in which the passkey to the best schools and the best jobs is no longer social background but high intelligence. At the bottom, the common denominator of the underclass is increasingly low intelligence rather than racial or social disadvantage. The Bell Curve describes the state of scientific knowledge about questions that have been on people's minds for years but have been considered too sensitive to talk about openly -- among them, IQ's relationship to crime, unemployment, welfare, child neglect, poverty, and illegitimacy; ethnic differences in intelligence; trends in fertility among women of different levels of intelligence; and what policy can do -- and cannot do -- to compensate for differences in intelligence. Brilliantly argued and meticulously documented, The Bell Curve is the essential first step in coming to grips with the nation's social problems.